Comorbidities as risk factors for clinical outcomes in pediatric patients with COVID-19: a comprehensive literature review - Saptadi Yuliarto; Kurniawan Taufiq Kadafi; Rakhman Tyas Perdana; Takhta Khalasha (Medical Faculty of Brawijaya University, Indonesia, 2022)
Background: The population that in a high risk to have a svere COVID-19 infection is children. The difficulties can influence the risk of controlling their hygiene and be worsened by the immaturity immune system, especially in children with comorbidities. Moreover, this problem needs to be prioritized in children. Despite in worldwide spread of severe COVID-19 infection, there are limited data regarding severe COVID-19 disease in children. Thus, we investigated the effects of comorbidities as risk factors for clinical outcomes in paediatric patients with COVID-19. Methods: This comprehensive literature review was from the PubMed, Google Scholar, and Science Direct databases through January 2021. The keywords used to obtain the literature include “COVID-19”, “coronavirus”, ” pediatric”, ”children”, ”severity”, ”comorbidity”, ”mortality”, ”death,” and “intensive”. The article with the inclusion criteria was involved. The information about the COVID-19 severity and underlying comorbidities in children were the main criteria that were enrolled. Results: The severe clinical risk factors in paediatric patients with COVID-19 that are reported most often are chronic lung disease (including asthma) (4312 critical patients), obesity (1007 critical patients), diabetes mellitus (815 patients), cardiovascular disorders (677 patients) and neurological disorders (542), prematurity (183 patients) and immunosuppression conditions including malignancy (143 patients). Other conditions in the form of hematological disorders, airway abnormalities, malnutrition and gastrointestinal disorders can also contribute to the clinical severity of paediatric COVID-19 patients. Conclusion: Children with underlying diseases such as obesity, chronic lung disease, cardiovascular disease, and neurologic disease had a higher risk of severe COVID-19 than children without comorbidities.